Roman Roads and Their Significance for the Economic Growth of the South of Upper Moesia - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The paper presents data that point to the routes of side roads (viae vicinales), less significant in terms of their construction, but, economically, highly important for the development of mining, trade, and craftsmanship in the south of Upper Moesia. Their significance is mirrored in the fact that they connected settlements or mining centres in the heartland of the province of Upper Moesia with superior main roads (previously mentioned) that criss-crossed Kosovo and Metohija (Naissus – Lissus, Narona – municipium DD – Scupi). The preserved fragments as well as the remains of large numbers of settlements outside of the area of main roads point out to their existence. In order to determine routes and study the road networks in Dardania, we used written ancient sources, itineraries and cartographic guides as well as few road remains and milestones from the territory. After using material evidence, the picture presenting the regional Roman road and newfound routes in the south of Upper Moesia is more reliable, i.e. new options for completely new interpretations relevant for the aforementioned problem can be suggested. The prevalent scientific method is based on historic sources and archeological and epighraph data from the territory.